Profil Keterampilan Penyelesaian Masalah Siswa melalui Penerapan Model Pembelajaran Problem Based Learning Ditinjau dari Perbedaan Gender - Yunita Roslina Ngongo; Ismail Efendi (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The purpose of this research is to describe the profile of students' problem solving skills through the application of problem based learning models in terms of gender differences. This type of research is descriptive qualitative research. The research population was seventh grade students of SMPN 3 Lingsar, West Lombok Regency. The research was conducted in March-May 2020. The research instrument used was a problem-solving skill test. The data collection technique used a test in the form of description questions. The data analysis technique used descriptive statistics. The results showed that the average mastery result of female students increased by 55.7, and the average mastery indicator of male students increased by 48.1. This shows that the problem solving skills of female students are greater than that of male students. The average score for male students is 0.99, in the high category, and the average score for female students is 0.93, in the high category. This shows that there are differences in problem solving skills between male and female students. The conclusion in this study is that the problem solving skills of female students are higher than that of male students.